Determining Citizens Eligibility for Cash Assistance Using the BORDA Method - Putra, Andriansyah; Sembiring, Muhammad Ardiansyah; Mardalius (JURNAL RISET KOMPUTER (JURIKOM), 2025)
The Bandar Lama Village Head Office has implemented a Direct Cash Assistance distribution system as an effort to help underprivileged people meet their daily needs. However, the selection process for aid recipients is still carried out manually and conventionally, which has the potential to cause inaccuracy in targeting, human error, and low time efficiency and accuracy of decision making. The absence of an integrated digital system and the use of selection methods that are not yet based on criteria weighting have caused inequality in the distribution of aid, leading to complaints from community members and ineffective program implementation. To overcome these problems, this study proposes the implementation of a web-based Decision Support System using the BORDA method. The BORDA method is a multi-criteria decision-making approach that allows for systematic evaluation of multiple criteria simultaneously, providing more objective and consistent results in the selection process. This system incorporates various socio-economic indicators such as income level, family size, housing conditions, and employment status to ensure comprehensive assessment of each applicant's eligibility. Based on the results of the BORDA method calculation on 30 tested resident data, it was obtained that a resident named Tomy had the highest score of 70, followed by Ranto Simanjuntak with a score of 70, and Marianik with a score of 67. With this BORDA method-based system, aid distribution in Bandar Lama Village can be carried out more accurately, fairly, and transparently, ultimately improving the effectiveness of social assistance programs and ensuring that aid reaches those who need it most.